Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 1-2 - Cumulative Review - Page 152: 15



Work Step by Step

Using the properties of equality, the solution to the given equation, $ 3(x+1)-2=8-5(x+7) $, is \begin{array}{l}\require{cancel} 3(x)+3(1)-2=8-5(x)-5(7) \\\\ 3x+3-2=8-5x-35 \\\\ 3x+5x=8-35-3+2 \\\\ 8x=-28 \\\\ x=-\dfrac{28}{8} \\\\ x=-\dfrac{\cancel{4}\cdot7}{\cancel{4}\cdot2} \\\\ x=-\dfrac{7}{2} .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.